Advanced microfluidic devices for fabricating multi‐structural hydrogel microsphere. Issue 3 (17th December 2021) - Chen, Zehao; Lv, Zhendong; Zhang, Zhen; Weitz, David A.; Zhang, Hongbo; Zhang, Yuhui; Cui, Wenguo
Abstract: Hydrogel microspheres are a novel functional material, arousing much attention in various fields. Microfluidics, a technology that controls and manipulates fluids at the micron scale, has emerged as a promising method for fabricating hydrogel microspheres due to its ability to generate uniform microspheres with controlled geometry. With the development of microfluidic devices, more complicated hydrogel microspheres with multiple structures can be constructed. This review presents an overview of advances in microfluidics for designing and engineering hydrogel microspheres. It starts with an introduction to the features of hydrogel microspheres and microfluidic techniques, followed by a discussion of material selection for fabricating microfluidic devices. Then the progress of microfluidic devices for single‐component and composite hydrogel microspheres is described, and the method for optimizing microfluidic devices is also given. Finally, this review discusses the key research directions and applications of microfluidics for hydrogel microsphere in the future. Abstract : The review summarizes the features of hydrogel microspheres and microfluidic technique, followed by the discussion of material selection in fabricating microfluidic device. Then the progress of microfluidic devices for both single‐component and composite hydrogel microspheres is described. Finally, this review discusses the key research direction and application of microfluidics for hydrogel microsphere in the future.